The Effects of Genre-Based Approach to Enhance Indonesian’s Students Writing - Nanda Listiyawati; Testiana Deni Wijayatiningsih; Riana Eka Budiastuti (Universitas Negeri Semarang, 2025)
This research scrutinizes the implementation of the Genre-Based Approach to enhance students’ writing recount performance and their perceptions of the learning experience. Employing a mixed-method research design, the study involved seventy-two of tenth-grade students in one of state school in Central Java. Quantitative data were collected through pretest and posttest to measure writing improvement, while qualitative data were obtained from a student’s questionnaire focusing on engagement, motivation, and comprehension. The data were analyzed using Shapiro-Wilk for normality, Levene’s test for homogeneity, and an independent samples t-test to compare the performance between the two groups. Descriptive analysis was applied to the questionnaire data. The results revealed the students in the experimental group showed notable improvement in writing performance after Genre-Based Approach intervention. In addition, students expressed positive perceptions of Genre-Based Approach, reporting increased comprehension, better retention, enhanced engagement, and strengthened critical thinking. These findings suggest that Genre-Based Approach supports writing development and fosters a more motivating and structured learning environment. This study contributes to the existing literature by highlighting Genre-Based Approach's academic and perceptual impacts, an area that remains underexplored in previous research.